FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN NON-KEUANGAN - Putri Angelita; Mungniyati (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study is to determine the effect of managerial ownership, institutional ownership, the board of directors, profitability, company size, leverage, operating cash flow, sales growth and company age on earnings management. This study used 114 non-financial companies that were listed consistently on the Indonesia Stock Exchange for the period 2019 to 2021. There are 342 data with 4 outlier data, therefore the data used in this study is 338 data. The sample selection technique used in this study was purposive sampling and used secondary data. The result shows that there is an influence between profitability, leverage and operating cash flow on profit management. Managerial ownership, institutional ownership, the board of directors, company size, sa